World Health Organization Disability Assessment Schedule versus Functional Independence Measure in Traumatic Brain Injury - Tarvonen-Schröder Sinikka; Koivisto Mari (Medical Journals Sweden, 2025)
Objective: In patients with traumatic brain injury, to compare functioning measured using the 12-item patient and proxy World Health Organization Disability Assessment Schedule (WHODAS-12) with assessments made by professionals.
Patients and methods: At discharge from rehabilitation, 89 consecutive patients with traumatic brain injury (10 mild, 36 moderate, 43 severe) and their proxies completed the WHODAS-12. Professionals assessed functioning simultaneously using the WHO minimal generic set of domains of functioning and health and Functional Independence Measure (FIM).
Results: From mild to severe traumatic brain injury, increasing disability was found in: sum, component and item scores of patient and proxy WHODAS, except for emotional functions in patients’ ratings; in sum and item scores of the WHO minimal generic data-set, except for pain; and in FIM total score and sub-scores. The WHODAS participation component was more impaired than activities. Although proxies rated functioning more impaired than patients, the correlation between patient and proxy WHODAS was strong (0.74). The correlation between patient/proxy WHODAS and FIM was also strong (–0.56 and –0.78, respectively). Proxy WHODAS differentiated mild and moderate traumatic brain injury more accurately than the other assessments.
Conclusion: We recommend using the WHODAS-12 when planning patient- and family-oriented rehabilitation services after traumatic brain injury.